Effect of adding various doses of clonidine as an adjunct in Transversus abdominis plane block in unilateral inguinal hernioplasty - Dhupia, Rakesh; Jain, Sunita; Sahani, Inder Singh; Modi, Vimal; Romday, Rakesh; Kothari, Archana (International Surgery Journal, 2017)
Background: Transverses abdominis plane (TAP) block is a new regional anaesthetic technique for postoperative analgesia in abdominal surgeries, as a part of multimodal analgesia. We evaluated effect of two different doses of clonidine as an adjunct in TAP block in patients underwent unilateral inguinal hernioplasty. Methods: Sixty adult patients undergoing unilateral inguinal hernioplasty were randomized into two groups, Group A (n=30) received bilateral TAP block with bupivacaine 0.25% 38cc + clonidine (1cc) 150 microgram +1cc NS=40cc, Group B (n=30) received bupivacaine 0.25% 38cc+clonidine (2cc) 300 microgram=40cc, at the end of surgery. The postoperative pain was evaluated by visual analog score (VAS) for pain scoring at 2, 4, 6, 12 and at 24 hours. Subjective assessment of duration of analgesia was done. Results: The VAS score in patients who received clonidine 300 microgram Group B as an adjunct was significantly lower than who received 150 microgram Group A. Duration of analgesia was longer in Group B. 2 patients in Group B showed bradycardia treated with atropine. Sedation score was lesser in Group A. Conclusions: Clonidine showed dose dependant analgesia and adverse effect in TAP block for postoperative analgesia. Higher doses of clonidine may be used as an adjunct in TAP block.